(untitled) (Bioscience Journal, 2019)
Currently, few active principles are authorized by the forest certification for the control of insect pests, with which it is necessary to develop new products, mainly aiming at lower environmental impact. The plants are able to develop substances called secondary metabolites, widely studied as an alternative form of pest control. Thus, the objective of this study was to evaluate the insecticidal potential of two Musa acuminata extracts, on the control of Atta sexdens rubropilosa. The extracts were obtained from the pseudostem of M. acuminata, which underwent drying and milling, producing two extracts: ethanolic (A1) and hydroethanolic rotaevaporate (A2) extract. For the analysis of the bioactivity of the extracts, a topical application of one milliliter of each extract on the ants was carried out, with the aid of spray, in the concentrations of: 2, 6, 10, 14, 18, and 20%, with distilled water (witness) applied to the test, analyzing the mortality and LC50, in different evaluation periods. At 24 hours the mortality of 90% at the concentration of 20% for the A1 extract was observed. From the 10% concentration there was 100% mortality in this same period for the A2 extract, and at 48 hours the 2% concentration caused 100% mortality. In the LC50 analysis for 24 hours values of 7.94 and 1.09% were obtained for ethanolic extract and rotavaporated ethanolic extract respectively. And the LC50 presented a decrease in values after 48 hours for the ethanolic extract presented value of 2.29%. Thus, it can be concluded that the A2 extract is the most efficient, since it allows the lower consumption of extract in the dilution for later application, due to the presence of insecticidal potential in low concentration.